AN ANALYSIS OF SLANG USED IN JUSTIN BIEBER SONG’S - Levie Meray; Nihta V. F. Liando; Tirza Kumayas (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The study's objective is to identify kinds of slang used in Justin Bieber's lyrics and the slang words used in them. The researcher analyzed the data using qualitative research. The author followed Bogdan and Biklen's (1992) suggested methods for analyzing the collected data. 30). The data were analyzed in four stages: unitization, categorization, explanation, and interpretation. The researcher used four steps to collect data: 1) Reading and comprehending the lyrics.2) determining which slang terms are utilized in the lyrics; 3) highlighting the slang terms in the lyrics; 4) identify and categorize slang terms' meanings. In light of the consequence of  information about shoptalk language in Justin Bieber melodies verse. following conclusions can be drawn from the research's findings and analysis:The slang used in a song not only teaches us new vocabulary but also new information. As a result, slang is one of our ways of expressing ourselves, teaches us about language and slang, and makes our songs interesting. Nowadays, slang is a part of language, so it is easy to understand and improve one's knowledge of slang. There is slang in movies, songs, tapes, journals, and the language of unique groups; however, it is important to know that slang is polite language used in conversation. By learning slang, the reader will understand the new language